(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article examines the technical and tactical aspects of relay running, the baton exchange mechanisms between runners, methods of reinforcing technique during training, and the role of team coordination. It emphasizes that running rhythm, arm coordination, and mutual trust among athletes are crucial for the efficiency of relay running. Scientific recommendations are provided on achieving optimal baton exchange speed within the three designated exchange zones.